THE LEADERS OF INTERNATIONAL FINANCIAL CENTERS: NEW YORK AND LONDON, AND THE EMERGING DYNAMIC FINANCIAL CENTER: SEOUL - Akhmadaliyeva Nikholakhon; Azamova Nafosatkhon (The Conference Hub, 2025)
This article aims to examine the meaning and importance of international financial centers, which play a crucial role in global economic growth and stability. It focuses on analyzing the positions and rankings of major cities in the Global Financial Centers Index (GFCI), providing statistical data to illustrate their competitiveness. The research highlights the strengths and advantages that make these cities attractive to investors and global businesses, including advanced financial infrastructure, innovation, and effective government policies. Moreover, the study considers the historical evolution of these financial hubs, showing how their past development has contributed to their current leadership. Special attention is given to the traditional leaders New York and London as well as the rapidly developing and dynamic financial center of Seoul, which is emerging as a new global player in international finance.
Keywords: New-York, London, Seoul, statistics, startups, international trade, history, innovation.